Improving Human Action Recognition Using Hierarchical Features And Multiple Classifier Ensembles. (18th November 2019) - Bulbul, Mohammad Farhad; Islam, Saiful; Zhou, Yatong; Ali, Hazrat
Abstract: This paper presents a simple, fast and efficacious system to promote the human action classification outcome using the depth action sequences. Firstly, the motion history images (MHIs) and static history images (SHIs) are created from the front (XOY), side (YOZ) and top (XOZ) projected scenes of each depth sequence in a 3D Euclidean space through engaging the 3D Motion Trail Model (3DMTM). Then, the Local Binary Patterns (LBPs) algorithm is operated on the MHIs and SHIs to learn motion and static hierarchical features to represent the action sequence. The motion and static hierarchical feature vectors are then fed into a classifier ensemble to classify action classes, where the ensemble comprises of two classifiers. Thus, each ensemble includes a pair of Kernel-based Extreme Learning Machine (KELM) or ${l}_{2}$ -regularized Collaborative Representation Classifier (${l}_{2}$ -CRC) or Multi-class Support Vector Machine. To extensively assess the framework, we perform experiments on a couple of standard available datasets such as MSR-Action3D, UTD-MHAD and DHA . Experimental consequences demonstrate that the proposed approach gains a state-of-the-art recognition performance in comparison with other available approaches. Several statistical measurements on recognition results also indicate that the method achieves superiority when the hierarchical features are adopted with the KELM ensemble. In addition, to ensure real-time processing capability of the algorithm, the running time of major components is investigated. Based on machine dependency of the running time, the computational complexity of the system is also shown and compared with other methods. Experimental results and evaluation of the computational time and complexity reflect real-time compatibility and feasibility of the proposed system.